KBG syndrome - Brancati Francesco; Sarkozy Anna; Dallapiccola Bruno (Orphanet Journal of Rare Diseases, 2006)
Abstract KBG syndrome is a rare condition characterised by a typical facial dysmorphism, macrodontia of the upper central incisors, skeletal (mainly costovertebral) anomalies and developmental delay. To date, KBG syndrome has been reported in 45 patients. Clinical features observed in more than half of patients that may support the diagnosis are short stature, electroencephalogram (EEG) anomalies (with or without seizures) and abnormal hair implantation. Cutaneous syndactyly, webbed short neck, cryptorchidism, hearing loss, palatal defects, strabismus and congenital heart defects are less common findings. Autosomal dominant transmission has been observed in some families, and it is predominantly the mother, often showing a milder clinical picture, that transmits the disease. The diagnosis is currently based solely on clinical findings as the aetiology is unknown. The final diagnosis is generally achieved after the eruption of upper permanent central incisors at 7–8 years of age when the management of possible congenital anomalies should have been already planned. A full developmental assessment should be done at diagnosis and, if delays are noted, an infant stimulation program should be initiated. Subsequent management and follow-up should include an EEG, complete orthodontic evaluation, skeletal investigation with particular regard to spine curvatures and limb asymmetry, hearing testing and ophthalmologic assessment.